A Political economic analysis of Original Pilipino Music and state policies promoting OPM - Conti, Mary June F. (University of the Philippines Diliman, 2015)
"Through a political economic perspective, I drew a historical analysis of state policies that promote the radio airplay of Original Pilipino Music (OPM). Focus interviews were used to trace initiatives to promote Filipino music through radio since the Martial Law years. Through oral accounts of key players in the radio industry, music industry, and the government, the study provides a grounded analysis of state regulation of the media amid efforts of radio stations and the music industry, both foreign and local, to promote their business interests. For instance, a quota on OPM songs is often rationalized in terms of cultural benefits. On the other hand, orders of such nature have been criticized as threatening the freedom of radio stations to air materials other than OPM which fit their respective program formats. Ultimately, stakeholders identify record sales and revenue from radio advertising as primarily at stake in the debate. By listening to FM stations and gathering quantitative data, the notion that the current policy is ineffective was supported. Results show that foreign songs still dominate the play lists, though specific programs have been devoted to OPM."